Plagues upon the earth : disease and the course of human history - Harper, Kyle, 1979- (Princeton economic history of the Western world, 2021)
"Plagues upon the Earth is a history of human civilization and the germs that have shaped its course. At every stage in our species' past, micro-organisms have had macro-effects on the development of human societies. Kyle Harper proposes the first history of human disease to make full use of a radical new source of evidence: pathogen genomes as a biological archive and window into prehistoric times. We can now begin to reconstruct the natural history of human disease at the molecular level, tracing the biographies of the viruses, bacteria, and protozoa that have haunted our species. The story reveals, Harper will show, the continuing importance of the deep past in determining the patterns of global divergence today. Plagues upon the Earth puts the dynamic two-way relationship between humanity and its germs in the foreground. The takeover and transformation of the planet by Homo sapiens has been the most powerful force shaping the evolution of microbial pathogens, and in turn, pathogen evolution has been a decisive influence on the destiny of human societies. From humanity's dispersal out of Africa to the rise of agriculture and complex civilizations, from the great pandemics of the medieval world to the age of global expansion and industrialization, from the modern increase in life expectancy to the ongoing threats of microbial resistance and emerging pathogens like HIV and Ebola, disease evolution has been and remains a primary, powerful, and unpredictable factor in human history. This will be the story of how we made our germs, and how our germs made the world as we know it. Harper aims to cover the entire timespan of Homo sapiens and to set the history of our species in deep perspective. The pathogens that exist today are the heirs of millions of years of evolution. Similarly, the patterns of economic development, and the roots of global inequality, have distant origins. Thus, Harper aims to bring together two bodies of literature: the history of disease and the study of geography and social development. The book is global in coverage, insisting on the importance of understanding how the tropics and temperate zones, the Old World and the New World, differ and interact throughout the course of history. Viruses, bacteria, and protozoa - in all their peculiarity and specificity - have played an enormous part in shaping the different outcomes experienced by human societies. Plagues upon the Earth combines biology, geography, and economics to understand these differences but emphasizes the central importance of evolution as a source of constant change. The past is always present in the history of disease, and the future is always unpredictable. The story continues right up to our own world. The book closes with a reflection on antibiotic resistance as a form of evolution that continues the ancient molecular antagonism between pathogens and host immune systems, and the importance of seeing this struggle in a broader environmental framework. Freedom from infectious disease remains an unachieved goal for our species, which is more interconnected than ever. The biology of infectious disease has been one of the great forces shaping the patterns of global development, but only with a sense of history - of the interplay of change, conjunction, and chance - can we begin to understand the intertwined story of human societies and their germs"--